2018
DOI: 10.4491/eer.2018.162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waste dumpsites on geotechnical properties of the underlying soils in wet season

Abstract: Indiscriminate disposal of waste and citation of open dumpsites are some of the key factors affecting the various soil geotechnical properties. Atterberg limit and consolidation tests were conducted to determine the effects of two open waste dumpsites (Uselu Market and New Benin) on geotechnical properties of their underlying soils. Soil sample collected from Uselu Market dumpsite in Benin City metropolis showed slightly lower hydraulic conductivity (K) of 1.0 × 10 -6 with plasticity index of 18.53% compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…there are dustbins and a site where plastics and other waste are burnt." This is despite several studies [48,49] highlighting that plastic waste incineration was a major source of air pollution, and~12% of plastics burnt released toxic pollutants which impact the climate, and threaten plant, animal and human health.…”
Section: Education and Awarenessmentioning
confidence: 99%
“…there are dustbins and a site where plastics and other waste are burnt." This is despite several studies [48,49] highlighting that plastic waste incineration was a major source of air pollution, and~12% of plastics burnt released toxic pollutants which impact the climate, and threaten plant, animal and human health.…”
Section: Education and Awarenessmentioning
confidence: 99%
“…The current annual reuse of ash worldwide ranges from 3% to 57%, depending on the country; however, it averages at approximately 16% [17], with the remainder sent to garbage dumps or landfills. Heavy metals, such as cadmium and lead, can easily leak from ash landfills into soil and groundwater, where they can remain as contaminants for thousands of years [18].…”
Section: Introductionmentioning
confidence: 99%
“…These heavy metals, which sedimented in soil matrix, restrict water movement through soil, reducing soil hydraulic conductivity [23]. Essienubong et al, [28] also indicated that the soil sample gathered from each of the Uselu Market and New Benin dumpsites presented lower hydraulic conductivity than the samples collected away from the dumpsites. This outcome might be because of clogging impact by organic waste that could happen because of the biological material build-up and growth of microorganisms during waste degradation.…”
Section: Hydraulic Conductivitymentioning
confidence: 99%
“…The age and type of the contaminants would impact the geotechnical characteristics of the soil well [22]. The studies performed by Raman & Sathiya Narayanan, [2], Ali et al, [9] Azeez et al, [10], Emeka et al, [11], Sharma et al, [14], Harun et al, [17], Thakur et al, [23], Sujatha et al, [24], Frempong & Yanful, [25], Nayak et al, [26], Mohammed et al, [27], Essienubong et al, [28] revealed that the physical and mechanical characteristics of contaminated soils were changed compared to the uncontaminated soils. Thus, assessing the impact of waste on soil engineering properties is an import issue and should be taken into consideration in the evaluation of the stability of landfill systems.…”
Section: Introductionmentioning
confidence: 99%